The Process Adoption And Diffusion Of Greenhouse Innovations Melon (Cucumis Melo L.) Culvation In Lamongan Regency - Rizqi Ardial Akbar; Kliwon Hidayat; Keppi Sukesi (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
Melon cultivation by farmers was initially only to fill empty land during the dry season because it was rain-fed land. After that, farmers continued even though it was not in the dry season because the price was high and stable. However, the results in the rainy season were not optimal, and pests were increasingly uncontrollable. Farmers continued to seek information and solutions until finally greenhouse technology emerged, but farmers needed a process to be able to optimise it. The objectives of this study were (1) to explain the adoption process of farmers in Lamongan Regency in accepting progress in greenhouse-based melon cultivation. (2) To explain the mechanism of greenhouse innovation diffusion in melon farming in Lamongan Regency. This study used a qualitative methodology. Determination of key informants using purposive sampling and for supporting informants using snowball sampling. Data collection techniques included observation, interviews, documentation, and literature reviews. The Miles and Huberman interactive model was used to analyse the data. The results of this study indicate that the adoption process of greenhouse innovation comes from farmers' initiatives to overcome the challenges of plant pests (OPT) and extreme climates. Farmers adopt this innovation optionally, and the majority of farmers continue to adopt it because of the more guaranteed production results. Some expand the scale of the greenhouse and market the results through agrotourism, social media, or cooperation with companies. However, some farmers do not continue due to limited capital and financial risks. The process of innovation diffusion is carried out through communication channels; one of the most effective is interpersonal communication, then through social media such as WhatsApp, Facebook, Instagram, and YouTube. The high initial capital for greenhouses is an obstacle for some farmers, so financial support, such as soft loans or subsidies from the government to increase adoption.